A cruz e os leões: uma leitura da carta de Santo Inácio de Antioquia a partir do conceito de animalidade na obra de Georges Bataille - Cunha, Roselaine Soares da (2009)
The objective of this work is to interpret the letters of Saint Ignacio of Antioquia (a christian martyr from the 1st century) in sight of the concept of Animality formulated by the french philosopher Georges Bataille. A scholar of the christian thought, Bataille dedicated himself at the lenght of his works (in the fields of philosophy, literature, petry and aesthetics) to investigate the existing relations between Erotism and religion. In the book entitled "Theory of religion", the french thinker develops the notion of Animality, investigating the basis of this primitive instinct (associated to death and sexual heat) and the straying process that it faced with the ascension of the christianism. He has among his pillars the belief on the ditachment of the sexual impulses as a mean to stray from that animal essence, that could dangerously insert us into a world of disorder. In the letter of Saint Ignacio of Antioquia, whose eagerness for the martydom was shown in his correspondence addressed to the christian communities of Rome, it is pointed out the need of a definitive separation from the Anomality that in the figure of Christ (Man-God) would be exterminated, conducting the Man to a sublime scope, apart from all impurity from the natural world. The reading of the letter of Saint Ignacio, under the philosophical vision of Bataille, will have the objective to aproximate the christian thought of the force that it so intensely denied; the Animality